Determinants of Fraudulent Financial Statements: Evidence from Fraud Hexagon and Corporate Governance Mechanism as Mediator - Ahmad Hafiz Zawawi; Roni Mulyatno (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This research investigates the impact of the Fraud Hexagon on financial statement fraud, utilizing corporate governance as a mediator. The research focuses on non-consumer cyclical manufacturers on the Indonesia Stock Exchange (IDX) from 2021-2024, involving purposive sampling. The test results show that Rationalization has a significant negative effect on Corporate Governance Mechanisms, while Ego has a significant positive effect; meanwhile, Pressure, Capability, Opportunity, or Collusion do not show a significant effect. Furthermore, regarding Fraudulent Financial Statements, Pressure, Capability, Rationalization, and Corporate Governance Mechanism were found to have a significant negative effect, while Opportunity had a significant positive effect; however, Ego or Collusion did not have a significant effect. The mediation test results indicate that Corporate Governance Mechanisms significantly mediate the effect of Ego in a negative direction and mediate the effect of Rationalization in a positive direction in Fraudulent Financial Statements; however, they do not mediate the effects of Pressure, Capability, Opportunity, and Collusion. These results validate that corporate governance effectiveness serves as a pivotal bridge between Fraud Hexagon elements and financial fraud. Nevertheless, as this research relies on structural metrics, further research is recommended to develop more substantive measures of governance that encompass the quality of implementation, ethical culture, and the effectiveness of oversight.